Relação entre os mecanismos inflamatórios da periodontite crónica e a doença cardiovascular - Leão, Sara Nogueira (2016)
Periodontal disease appears to have an important role as a risk factor for the onset of certain systemic diseases such as cardiovascular diseases. This relationship is based mainly in the invasion of periodontal microorganisms into the bloodstream through the inflamed periodontal tissues. Both diseases are characterized by inflammatory processes, and are risk factors, and they age, sex, education level, smoking and drinking habits, hypertension, stress, depression, low levels of HLD and diabetes. The association between the periodontal disease and the cardiovascular disease has been extensively studied due to the influence of inflammation in atherosclerotic pathology. Since these diseases are increasingly common, quantify their association is of great relevance to public health. Objective: The objective of this study is to conduct a bibliographic review in order to investigate whether there is an association between cardiovascular disease and chronic periodontal disease, and realize the state of the art. Conclusion: The literature review indicates that there is a strong but not conclusive association between periodontal disease and cardiovascular disease. It is therefore necessary to further research on the subject that will allow us to not only understand the mechanisms involving both diseases but also to reach a form of intervention in its development.